2009
DOI: 10.1139/w09-011
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity of soil samples from the western Himalayas, India

Abstract: High-altitude cold habitats of the Himalayas are little explored with respect to bacterial diversity. Diverse bacterial species and phylotypes obtained by culture-dependent and culture-independent approaches are reported here. Phylogenetic analysis and modulation of bacterial diversity with altitude and available organic carbon content are also described. Psychrophilic and psychrotolerant bacteria dominated the Himalayan habitats, accounting for 60% of the cultivated strains. Isolates produced one or more (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Nemergut et al (2007) who studied the development of microbial communities along a receding glacier in Peru reported not just an increase in the complexity of the microbial communities with soil age but also an overall increase in similarity between the communities in the young soil to that of a mature soil with age. Similarly, Gangwar et al (2009) could show an increase in both bacterial population size and diversity with increasing altitude in Western Himalayian mountain tops. A similar trend was reported for the Rocky Mountains (Bryant et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…Nemergut et al (2007) who studied the development of microbial communities along a receding glacier in Peru reported not just an increase in the complexity of the microbial communities with soil age but also an overall increase in similarity between the communities in the young soil to that of a mature soil with age. Similarly, Gangwar et al (2009) could show an increase in both bacterial population size and diversity with increasing altitude in Western Himalayian mountain tops. A similar trend was reported for the Rocky Mountains (Bryant et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…Similar results were found with non-culture based assessment of bacterial communities at the sites investigated in this study in spring: the highest bacterial richness and diversity was found at the site at the lowest altitude (Siles and Margesin 2016). Distinct microbial community structures correlating with altitude have been observed in subalpine and alpine environments (Lipson 2007), Himalayan slopes (Gangwar et al 2009) and in Indian (Ma et al 2004), Chinese (Xu et al 2015) and Peruan mountains (Fierer et al 2011) among others.…”
Section: Discussionmentioning
confidence: 99%
“…Inverse correlations between bacterial community abundance and altitude were also found in Chinese and Indian mountain slopes (Ma et al 2004). Culture-independent approaches revealed a dominance of Betaproteobacteria at higher altitudes in western Himalayas, India, while Gammaproteobacteria , Bacteroidetes and lower proportions of Gram-positive bacteria (mainly Firmicutes ) dominated the culturable community (Gangwar et al 2009). However, others concluded that microbial diversity was not significantly altered across a montane elevational gradient in eastern Peru, using a barcoded pyrosequencing procedure, in opposition to the drastic changes observed for plant and animal taxa (Fierer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The strains were selected from the set of 173 cultured and uncultured bacteria obtained from various environmental samples from Western Himalayas on the basis of their novelties both at 16S rRNA gene sequence and phenotypic level [7].…”
Section: Resultsmentioning
confidence: 99%
“…The cultured bacterial strains belonged to Protobacteria (largely gamma-Proteobacteria), Firmicutes, Actinobacteria, and Bacteroidetes [7]. Most of the strains belonged to the genus Bacillus (30%), followed by Pseudomonas (24%), Arthrobacter (12%), and Flavobacterium (6%).…”
Section: Introductionmentioning
confidence: 99%